Kategorisasi Media Siber Hulondalo.Id dalam Framing Pemberitaan Kekerasan Dalam Rumah Tangga Di Gorontalo - Noval Sufriyanto Talani; Rahmatiah Rahmatiah; Ferdinand Kerebungu; Dondick Wicaksono Wiroto (Communicatus: Jurnal Ilmu komunikasi, 2023)
As an event that grabs the public's attention, domestic violence (KDRT) is still making headlines in various mass media lines, including cyber media. This study aims to identify cases of domestic violence reported by the cyber media Hulondalo.Id and describe the categorization patterns made by the media to frame domestic violence events in Gorontalo. The method used in this study is a qualitative method with a framing analysis tool from Murray Edelman. The results showed that the cases of domestic violence published by the cyber media Hulondalo.Id were quite diverse. In the news, certain categorizations are formed for perpetrators and victims of domestic violence. This form of categorization becomes a pattern of media framing of cases of domestic violence that occurred in Gorontalo. The pattern made by Hulondalo.Id places the perpetrators as coercive, drunken, sadistic, barbaric, and persecuting figures. Meanwhile, the victim is positioned as a helpless figure, a patient young wife, and a poor woman. Ideologically the media position themselves as siding with the victim. But the textual facts prove that the Hulondalo.Id cyber media tends to exploit the identity of the victim rather than the identity of the perpetrators of domestic violence.